Designing magnetocaloric materials for hydrogen liquefaction with light rare-earth Laves phases - Wei Liu; Tino Gottschall; Franziska Scheibel; Eduard Bykov; Nuno Fortunato; Alex Aubert; Hongbin Zhang; Konstantin Skokov; Oliver Gutfleisch (JPhys Energy, 2023)
Magnetocaloric hydrogen liquefaction could be a ‘game-changer’ for liquid hydrogen industry. Although heavy rare-earth based magnetocaloric materials show strong magnetocaloric effects in the temperature range required by hydrogen liquefaction (77–20 K), the high resource criticality of the heavy rare-earth elements is a major obstacle for upscaling this emerging liquefaction technology. In contrast, the higher abundances of the light rare-earth elements make their alloys highly appealing for magnetocaloric hydrogen liquefaction. Via a mean-field approach, it is demonstrated that tuning the Curie temperature ( T _C ) of an idealized light rare-earth based magnetocaloric material towards lower cryogenic temperatures leads to larger maximum magnetic and adiabatic temperature changes (Δ S _T and Δ T _ad ). Especially in the vicinity of the condensation point of hydrogen (20 K), Δ S _T and Δ T _ad of the optimized light rare-earth based material are predicted to show significantly large values. Following the mean-field approach and taking the chemical and physical similarities of the light rare-earth elements into consideration, a method of designing light rare-earth intermetallic compounds for hydrogen liquefaction is used: tuning T _C of a rare-earth alloy to approach 20 K by mixing light rare-earth elements with different de Gennes factors. By mixing Nd and Pr in Laves phase (Nd, Pr)Al _2 , and Pr and Ce in Laves phase (Pr, Ce)Al _2 , a fully light rare-earth intermetallic series with large magnetocaloric effects covering the temperature range required by hydrogen liquefaction is developed, demonstrating a competitive maximum effect compared to the heavy rare-earth compound DyAl _2 .